Exogenous RNA as a Regulatory Signal during a Plant’s Interaction with the Biotic Environment: An Evolutionary Perspective and Future Applications in Agriculture - Ivashuta, Sergey (Plants (Basel), 2021)
Environmental RNAi (eRNAi) is a sequence-specific regulation of endogenous gene expression in a responsive organism by exogenous RNA. While exogenous RNA transfer between organisms of different kingdoms of life have been unambiguously identified in nature, our understanding of the biological significance of this phenomenon remains obscure, particularly within an evolutionary context. During the last decade multiple reports utilizing various mechanisms of natural eRNAi phenomena have been attempted to develop new agricultural traits and products including weed, disease and insect control. Although these attempts yielded mixed results, this concept remains extremely attractive for many agricultural applications. To better utilize eRNAi for practical applications, we would like to emphasize the necessity of understanding the biological significance of this phenomenon within an evolutionary context and learn from nature by developing advanced tools to identify and study new cases of exogeneous RNA transfer and eRNAi. In this opinion article we would like to look at the exogeneous RNA transfer from an evolutionary perspective, propose that new cases of exogeneous RNA transfer still remain to be identified in nature, and address a knowledge gap in understanding the biological function and significance of RNA transfer. We believe such approach may eventually result in a more successful use of this phenomenon for practical applications in agriculture.